Microstructure and mechanical properties of the joint prepared by diffusion bonding on an advanced PM Ni based superalloy. (December 2022) - Liu, Guangxu; Lin, Fangrui; Yang, Jie; Wang, Xiaofeng; Zou, Jinwen
Abstract: In this study, an advanced powder metallurgy (PM) Ni based superalloy was successfully diffusion bonded. Microstructure of the joints was characterized by scanning electron microscope, electron backscatter diffraction and transmission electron microscopy; mechanical properties of the joints were evaluated by tensile test. When bonded without interlayer, many microvoids and a planar bond line were found at the interface, resulting in the low ultimate tensile strength (UTS, 1071 MPa) and elongation (EL, 3.4%) of the joint. Besides, weakly bonded areas appeared at the smooth fracture surface. When 5 μm-thick-Ni foil was used as the interlayer, microvoids were still observed at the joint. In addition, a carbide depleted zone and massive γ′ precipitates occurred at the interface. Tensile test showed that the UTS (1266 MPa) and EL (8.2%) of the joint increased slightly, but discontinuous weakly bonded areas and microvoids were observed on the fracture surface. As 2 μm-thick-Ni coating was used, a soundly bonded joint without microvoid was obtained. However, the carbide depleted zone and γ′ precipitates still existed at the interface. Tensile test showed that the UTS (1386 MPa) and EL (12.8%) of the joint increased dramatically, and plenty of dimples appeared on the fracture surface. Highlights: Microvoids were found on joints bonded without interlayer and with 5 μm Ni foil. Microvoids were eliminated when 2 μm Ni coating was used as the interlayer. γ′ and carbide depleted zones appeared on joints bonded with Ni foil and coating. Joint bonded with 2 μm Ni coating showed highest strength and ductile fracture mode.